THE EFFECT OF IMAGERY AND SELF-TALK TRAINING WITH SINGLE TARGET AND TARGET TRAINING IS HINDERED ON INCREASING THE SHOOTING ACCURACY OF A DISTANCE OF 7 METERS IN PETANQUE AT THE EAST JAVA PUSLATDA - Ika Ana, Kholifatul; Nurkholis; Siantoro, Gigih; Zulfikar Rizki, Ainun (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
The purpose of this study is to determine the influence of the application of imagery training during shooting exercises at a distance of 7 meters with single targets and targets unable at PUSLATDA JATIM, knowing the influence with the application of self-talk exercises during shooting exercisesa distance of 7 meters with a single target and an obstacle target at PUSLATDA JATIM, Knowing the mental differences of PUSLATDA JATIM athletes after receiving mental imagery and self-talk training. This research is an experimental study. The result of this study is that there is a significant effect of imagery training on the results of single target shooting and obstacle target shooting. There is a significant effect of self-talk training on the results of single target shooting and obstacle target shooting. This research requires further research on shooting practice , especially single target shooting practice and target shooting with different sample and population conditions. As in Exercise, imagery and self-talk can be used in certain sports in athletes or sports organizations to improve ability or accuracy..